Development of Career Path Planning and Learning Motivation in Vocational School Students - Arifin, M. Zainal; Muhammad Yusuf; Maskuri (Yayasan Payungi Smart Madani, 2024)
Islamic boarding schools are a form of education that combines formal education with religious education. Apart from being included in the religious education curriculum, extra activities are also provided, this can be done because students live or live in a dormitory in the same area. With busy activities, students often experience boredom, which students at the Darut Taqwa Dlanggu Mojokerto Islamic Boarding School also experience. The result of the boredom experienced is a decrease in students' learning motivation; some students even choose to run away from the boarding school. Apart from the problem of decreasing motivation to learn, another problem faced is the lack of extensive exploration by students regarding career planning after completing their education at the boarding school. After graduating, some of them continued their studies, with their chosen majors being religion and education, while others chose to work and get married. This service activity aims to increase learning motivation and provide career planning to Darut Taqwa Islamic Boarding School students; the activity is carried out in the form of mentoring, where students are given an understanding of motivation and career planning. A follow-up step to this activity was a Forum Group Discussion (FGD) as a forum for sharing and discussion to help resolve problems related to students' career paths. This is intended to help map goals and get to know the various career options and college majors that can be taken after graduating from Islamic boarding school